Radiogenomics nomogram based on MRI and microRNAs to predict microvascular invasion of hepatocellular carcinoma - Hu, Guangchao; Qu, Jianyi; Gao, Jie; Chen, Yuqian; Wang, Fang; Zhang, Haicheng; Zhang, Han; Wang, Xuefeng; Ma, Heng; Xie, Haizhu; Xu, Cong; Li, Naixuan; et al. (Frontiers in Oncology, 2024)
Purpose: This study aimed to develop and validate a radiogenomics nomogram for predicting microvascular invasion (MVI) in hepatocellular carcinoma (HCC) on the basis of MRI and microRNAs (miRNAs).This cohort study included 168 patients (training cohort: n = 116; validation cohort: n = 52) with pathologically confirmed HCC, who underwent preoperative MRI and plasma miRNA examination. Univariate and multivariate logistic regressions were used to identify independent risk factors associated with MVI. These risk factors were used to produce a nomogram. The performance of the nomogram was evaluated by receiver operating characteristic curve (ROC) analysis, sensitivity, specificity, accuracy, and F1-score. Decision curve analysis was performed to determine whether the nomogram was clinically useful.The independent risk factors for MVI were maximum tumor length, rad-score, and miRNA-21 (all P < 0.001). The sensitivity, specificity, accuracy, and F1-score of the nomogram in the validation cohort were 0.970, 0.722, 0.884, and 0.916, respectively. The AUC of the nomogram was 0.900 (95% CI: 0.808-0.992) in the validation cohort, higher than that of any other single factor model (maximum tumor length, rad-score, and miRNA-21).The radiogenomics nomogram shows satisfactory predictive performance in predicting MVI in HCC and provides a feasible and practical reference for tumor treatment decisions. 删除了: To the authors' knowledge, no study has predicted MVI in 129 HCC by combining miRNAs with radiomics. Five kinds of miRNAs 130 (miR-21/miR-26a/miR-27a/miR-122/miR-223) from plasma of 131 patients, which have been shown to be associated with HCC (17, 18) 132 删除了: Included patients were randomly divided into training and 133 validation cohorts according to a 7:3 ratio. The flowchart of patient 134 enrollment and grouping in Fig. 1. All patients received routine 135 laboratory tests and plasma miRNA examinations prior to curative 136 resection. The patients' basic data included routine laboratory tests 137 and plasma miRNAs. Further information on the patients is 138 available in Table 1.